1989
DOI: 10.1093/infdis/160.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Otitis Media During the First Seven Years of Life in Children in Greater Boston: A Prospective, Cohort Study

Abstract: To determine the epidemiology of acute otitis media (AOM) and duration of middle ear effusion (MEE), we followed consecutively enrolled children from shortly after birth until 7 y of age. Because some children dropped out of the study, data were analyzed for 877 children observed for at least 1 y; 698 were observed for at least 3 y, and 498 were observed until 7 y of age. By 1 y of age, 62% of the children had greater than or equal to 1 episode of AOM and 17% had greater than or equal to 3 episodes; by 3 y of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
775
3
55

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,321 publications
(876 citation statements)
references
References 26 publications
43
775
3
55
Order By: Relevance
“…studies published recently. 3,6,7 These studies indicate a beneficial effect of breastfeeding (even for short durations) on reducing AOM episodes in infancy. Day care outside the home was an important risk factor in our study and has been reported to be a significant risk factor for AOM in larger cohorts described in metaanalytic reports.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…studies published recently. 3,6,7 These studies indicate a beneficial effect of breastfeeding (even for short durations) on reducing AOM episodes in infancy. Day care outside the home was an important risk factor in our study and has been reported to be a significant risk factor for AOM in larger cohorts described in metaanalytic reports.…”
Section: Discussionmentioning
confidence: 67%
“…2 In Greater Boston, among 877 children still being followed at 1 year of age, breastfeeding was found to be significantly protective for one or more episodes (odds ratio ϭ 0.64; 95% confidence interval [CI]: .44-.91). 3 In another large cohort of 2130 children still being followed at 2 years, breastfeeding for Ͻ3 months was associated with a 20% to 60% elevated risk of AOM and OME. 4 A metaanalysis of recent follow-up studies concluded that breastfeeding even for 3 months was protective in decreasing the risk of OM.…”
mentioning
confidence: 98%
“…O.M. is more common among males than among females (Casselbrant et al, 1985;Teele et al, 1989 The pathology of sensorineural hearing loss resulting from otitis media was assessed by Paparella et al (1972), Goycoolea et al (1980) and walby et al (1983). The round window membrane was a site of pathological involvement, especially in C.S.O.M.…”
Section: Type Of Hearing Lossmentioning
confidence: 99%
“…OM (Otitis Media, middle ear infection) is amongst the most common of childhood infections—83% of children have at least one episode by 3 years old and 46% have multiple episodes (Teele, Klein, & Rosner, 1989). Acute cases can result in accumulation of fluid in the middle ear (OM with Effusion), causing temporary mild‐moderate hearing loss (Winskel, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Teele et al. (1989) found that OM in the first 3 years of life correlated with impairments in grammatical morphology at age 7. However, Luotonen et al.…”
Section: Introductionmentioning
confidence: 99%